The Effect of Sustainability Certification Towards Firms’ Profitability: The Case of Malaysian Shariah Compliant Palm Oil Companies - Shahimi, Shahida; Fuad, Siti Hanisah (Journal of Social Transformation and Regional Development, 2023)
In Islam, the preservation of environment is one of the fundamental in maqasid al-shariah (objectives of shariah). As world’s leading hub of Islamic finance and the second largest palm oil producer, a positive respond on environment preservation had been given by Malaysia towards sustainable palm oil industry. Moreover, almost 70% of Malaysian palm oil companies are complied with shariah. It is necessary to the shariah compliant companies to put into consideration regarding environment sustainability in their main objective of the firms. Therefore, Malaysia urges these companies to adopts Roundtable on Sustainable Palm Oil (RSPO) and Malaysian Sustainable Palm Oil (MSPO) certifications which ensure sustainable operation and production of certified palm oil. However, these companies have concern on profitability over sustainability due to additional cost to subscribe the certification. Therefore, this study is conducted to identify the effect of the sustainability certification on the profitability of 29 shariah-compliant palm oil companies listed in Bursa Malaysia from 2013 to 2017. It is important to provide evidence on certified companies’ profitability to encourage more adoption of sustainability certification, promote sustainable practices and increase production certified palm oil among shariah compliant companies. The results of generalized least squares (GLS) regression show that certified companies enjoy profits that are 2.3% higher than those of non-certified companies. These findings support the sustainability policy in palm oil industry by the Malaysian through MSPO certification which became mandatory in late 2019.